International Pooling of Operators' Funds An Option to Increase the Amount of Financial Security to Cover Nuclear Liability? - Pelzer, Norbert (OECD Publishing, 2012)
Financial security to cover the third party liability of the operators of nuclear installations is nearly exclusively provided by the insurance industry. The recent revision exercises of the international nuclear liability conventions resulted in higher liability amounts and in a broader concept of compensable nuclear damage. This marks a new challenge for the insurance industry: its financial capacity is not unlimited, and there seems to emerge difficulties to cover the new liability in full